#1**+1 **

x + 3y = - 3 |*(-1)

4x + 3y = 6

- x - 3y = 3

__4x + 3y = 6__

3x = 9 | : 3

** x = 3 **

3 + 3y = - 3 | - 3

3y = - 6 | : 3

**y = 2**

Omi67
Oct 18, 2017

#2**+1 **

Okay, so we begin by picking one of the equations, and solving for either x or y.

I will pick equation 1, and solve for x:

\(x=-3-3y.\)

We now insert this modifyed version of equation 1 into equation 2. By that i mean that we replace x in equation 2 with -3-3y. We do this and obtain:

\(4\cdot(-3-3y)+3y=6\)

which gives us that

\(y=-2.\)

What remains now is to replace y with -2 in any of our expressions that contain both x and y. Its the easiest to insert it into x=-3-3y, since we would otherwise have to solve for x again! We do this and obtain;

\(x=-3-3\cdot(-2)=3.\)

Guest Oct 18, 2017